Expanding the reactivity of inorganic clusters towards proteins: the interplay between the redox and hydrolytic activity of Ce(iv)-substituted polyoxometalates as artificial proteases. Issue 31 (16th July 2021) - Abdelhameed, Shorok A. M.; Ly, Hong Giang T.; Moons, Jens; de Azambuja, Francisco; Proost, Paul; Parac-Vogt, Tatjana N.
Abstract : The redox chemistry of Ce IV -polyoxometalates towards proteins is linked to the redox-active residues on protein surface. It can be tuned by adjusting reaction parameters, directly impacting its efficiency and selectivity as an artificial protease. Abstract : The ability of soluble metal-oxo clusters to specifically interact with protein surfaces makes them attractive as potential inorganic drugs and as artificial enzymes. In particular, metal-substituted polyoxometalates (MS-POMs) are remarkably selective in hydrolyzing a range of different proteins. However, the influence of MS-POMs' redox chemistry on their proteolytic activity remains virtually unexplored. Herein we report a highly site-selective hydrolysis of hemoglobin (Hb), a large tetrameric globular protein, by a Ce(iv )-substituted Keggin polyoxometalate (Ce IV K), and evaluate the effect of Ce IV K's redox chemistry on its reactivity and selectivity as an artificial protease. At pH 5.0, incubation of Hb with Ce IV K resulted in strictly selective protein hydrolysis at six Asp-X bonds, two of which were located in the α-chain (α(Asp75-Leu76) and α(Asp94-Pro95)) and five at the β-chain (β(Asp51-Ala52), β(Asp68-Ser69), β(Asp78-Asp79), β(Asp98-Pro99) and β(Asp128-Phe129)). However, increasing the pH of the reaction mixture to 7.4 decreased the Ce IV K hydrolytic reactivity towards Hb, resulting in the cleavage of only one peptide bond (β(Asp128-Phe129)). Combination of UV-Vis, circular dichroism and Trp fluorescence spectroscopy indicated similar interactions between Hb and Ce IV K at both pH conditions; however, 31 P NMR spectroscopy showed faster reduction of Ce IV K into the hydrolytically inactive Ce III K form in the presence of protein at pH 7.4. In agreement with these results, careful mapping of all hydrolyzed Asp-X bonds on the protein structure revealed that the lower reactivity toward the α-chain was consistent with the presence of more redox-active amino acids (Tyr and His) in this subunit in comparison with the β-chain. This points towards a link between the presence of the redox-active sites on the protein surface and efficiency and selectivity of redox-active MS-POMs as artificial proteases. More importantly, the study provides a way to tune the redox and hydrolytic reactivity of MS-POMs towards proteins through adjustment of reaction parameters like temperature and pH.